2010
DOI: 10.1111/j.1365-3148.2010.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the clinical transfusion practice at a regional referral hospital in Uganda

Abstract: The aim of this study was to determine the indications for transfusion, blood ordering practices and post-transfusion complications, and to assess the clinical transfusion practice at Mbarara Regional Referral Hospital (MRRH) in Mbarara, Uganda. There are no guidelines on the appropriate use of blood at MRRH. Therefore, there was a need to assess the local clinical transfusion practice. Patients' hospital files were studied for evidence of blood transfusions in 2008. All five wards were reviewed and details on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
45
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 3 publications
7
45
3
Order By: Relevance
“…The Kampala study also found similar findings including a higher percentage of female transfusion recipients and obstetrics, gynecology, and medical wards as the top users of blood issued. Another Ugandan study from a regional referral hospital found a mean number of 1.7 units requested per recipient, similar to 1.3 units in our study, and also that most patients received WB transfusions [20]. Unlike our study, a study of blood transfusion services at a district hospital in Malawi during 1 month reported a higher percentage of pediatric transfusions (57%) compared with 34% in our study [29], which may be due to our more representative sample of hospitals and seasons.…”
Section: Discussionsupporting
confidence: 87%
“…The Kampala study also found similar findings including a higher percentage of female transfusion recipients and obstetrics, gynecology, and medical wards as the top users of blood issued. Another Ugandan study from a regional referral hospital found a mean number of 1.7 units requested per recipient, similar to 1.3 units in our study, and also that most patients received WB transfusions [20]. Unlike our study, a study of blood transfusion services at a district hospital in Malawi during 1 month reported a higher percentage of pediatric transfusions (57%) compared with 34% in our study [29], which may be due to our more representative sample of hospitals and seasons.…”
Section: Discussionsupporting
confidence: 87%
“…In most developed countries, LD red cell concentrates resuspended in additive solutions are the state-of-the-art red cell products for allogeneic transfusion. However, the results of this study are still valuable for autologous transfusion and the many clinical settings, particularly in developing countries [35] where allogeneic whole blood is still mainly employed. Furthermore, the use of whole blood is gaining renewed interest in developed countries [36][37][38] because it has been shown that leukocyte depletion results in a considerably improved plasma quality in whole blood [39].…”
Section: Discussionmentioning
confidence: 99%
“…WB has been the mainstay in blood transfusion for many decades but has nowadays largely been replaced by component transfusion in industrialized countries 22 . However, WB is still being extensively used in autologous transfusion and in allogeneic transfusion in developing countries 9 . In addition, WB has regained interest as the blood product of choice for various clinical situations (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the quality of WB cannot be addressed using apheresis RBCs. Since WB is still widely used in autologous transfusion, and in many undeveloped countries also in allogeneic transfusions, 9 though, data on the quality of this blood product in particular are needed. Furthermore, WB has gained renewed interest in industrialized countries recently, 10‐12 because it has been shown that leukoreduction results in a considerably improved plasma quality of WB, 13 possibly rendering it suitable particularly for use in massive transfusion settings.…”
mentioning
confidence: 99%